Markets for Promoting Innovation in Health Care? A Market Practice Study of Public Procurement of Innovation (PPI) - Özbek, Nurgül; Krafve, Linus Johansson; Kjellberg, Hans; Sjögren, Ebba (NOvation — Critical Studies of Innovation, 2023)
This article critically analyzes public procurement of innovation (PPI) as an instance of using markets or market-like aspects as a means to resolve public concerns. It reports findings from a case of procuring radiation therapy equipment for a university hospital in Stockholm, Sweden. By extending a line of literature built on economic sociology as well as science and technology studies (STS), the study elaborates on public actors’ efforts in framing markets to promote innovation. The case illustrates how the participating actors constructed the notion of innovativeness to be introduced into health care as means of addressing various public concerns. It also reveals the intended—and unintended—consequences of PPI as manifested in various actors’ claims on the value of PPI realized in practice. The study suggests that it is extremely difficult to frame a market for the realization of innovation via procurement as a policy instrument because we cannot predict the ultimate impacts of devices and practices employed in such initiatives. By formulating a practice-based critique of PPI, our study invites important questions about the potentiality of such instruments for governing innovation without delimiting their consequences to the success-or-failure dichotomy as prescribed in predefined tools and strategies.